2015
DOI: 10.1159/000380770
|View full text |Cite
|
Sign up to set email alerts
|

Neural Tube Defects in Jarcho-Levin Syndrome: Study of Twenty-Eight Cases

Abstract: Jarcho-Levin syndrome (JLS) is a congenital disorder consisting of various vertebral and costal anomalies. Congenital heart defects, abdominal wall malformations, urogenital and anal abnormalities, multiple skeletal anomalies, upper limb anomalies, spina bifida, and inguinal, umbilical and diaphragmatic hernias can be seen as components of JLS. Spina bifida appears to be a common finding in reported JLS cases. We retrospectively reviewed the medical records, plain X-rays and MRIs of patients with spina bifida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…Another study 18 has reported the presence of neural tube defects in 4 cases of prenatally diagnosed Jarcho–Levin syndrome. Alatas et al 24 have reported that 28 patients with Jarcho–Levin syndrome, of the cases; 26 had patients who were meningmyelocele, 16 had patients who were hydrocephalus, and varies central nervous system anomalies in other cases. Also in this series, all cases had meningmyelocele.…”
Section: Discussionmentioning
confidence: 99%
“…Another study 18 has reported the presence of neural tube defects in 4 cases of prenatally diagnosed Jarcho–Levin syndrome. Alatas et al 24 have reported that 28 patients with Jarcho–Levin syndrome, of the cases; 26 had patients who were meningmyelocele, 16 had patients who were hydrocephalus, and varies central nervous system anomalies in other cases. Also in this series, all cases had meningmyelocele.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need for neurosurgeons and urologists to comprehensively evaluate these children, and inform their families of their condition and prognosis. As shown in previous studies, for children with bladder ectropion, bladder duplication, hypospadias and cryptorchidism, it's suggested to give them surgical therapy during their childhood [18]. Although these urogenital malformations did not progress and no complications occurred during the follow-up, long-term prognoses are needed through further follow-ups.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, although renal dysplasia is often asymptomatic, hypertension can be caused by vascular malformation [13]. in the process of embryonic development, the skeletal muscle system was also homologous with the urogenital system that originated from the mesoderm, and the development time is also in the early embryo [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Other abnormalities have also been described in Jarcho-Levin syndrome, including neural tube defects, Arnold-Chiari malformation, renal/urinary tract abnormalities, hydrocephalus, hydroureteronephrosis, and myelomeningocele. 3 This set of particular presentations is usually identified in a newborn. Jarcho and Levin first report it in 1938.…”
Section: Introductionmentioning
confidence: 99%